On the fundamental theorem of asset pricing: random constraints and bang-bang no-arbitrage criteria - Igor V. Evstigneev; Klaus Schürger; Michael I. Taksar (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
The paper generalizes and refines the Fundamental Theorem of Asset Pricing of Dalang, Morton and Willinger in the following two respects: (a) the result is extended to a model with portfolio constraints; (b) versions of the no-arbitrage criterion based on the bang-bang principle in control theory are developed.
Keywords: G13; G12; D40; 330; no arbitrage criteria; portfolio constraints; supermartingale measures; bang-bang control; Capital Asset Pricing Model; Portfolio-Management; Martingale; Kontrolltheorie; Arbitrage Pricing; Theorie